Pengelolaan Keuangan Sekolah : Sumber Pembiayaan dan Pertanggungjawaban dalam Satuan Pendidikan - Yosi Sisri Nengsi; Difa Maulidika; Ahmad Sabri; Rully Hidayatullah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze school financial management, focusing on sources of financing and accountability mechanisms in educational institutions. Through the literature study method, this study explores various important aspects related to school financial administration, including the diversity of funding sources, the role of financial managers, and the accountability measures needed to ensure the transparent and efficient use of funds. The findings show that effective financial management has a great influence on the quality of education. Additionally, the study identifies the challenges schools face in financial management, providing valuable insights for policymakers, educators, and administrators seeking to improve financial practices in schools. The results of this research are expected to contribute to the development of a more comprehensive conceptual framework on school financial management in Indonesia.